Preliminary phytochemical screening and biological investigation of methanol and hexane extracts of Borreria Pusilla - Keya, Shakera Islam (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.